Cover, Content, and Editorial Note from Borneo J Pharm Vol. 4 No. 2 May 2021 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2021)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm), has been published in May 2021. Starting from this volume, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve the circulation of the best articles published by Borneo J Pharm. This edition contains ten articles consisting of Pharmacology-Toxicology, Pharmaceutical, Microbiology Pharmacy, and Clinical-Community Pharmacy. This edition includes writings from seven countries including Indonesia, India, Pakistan, Iran, Nepal, Uganda, and Nigeria. The authors come from several institutions, including Sekolah Tinggi Ilmu Kesehatan Borneo Lestari, Bandung Institute of Technology, Universitas Lambung Mangkurat, Universitas Muhammadiyah Banjarmasin, Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, Shri Gopichand College of Pharmacy, Government College University Faisalabad, Islamic Azad University, Sardar Patel College of Pharmacy, Universal College of Medical Sciences, NKBR College of Pharmacy and Research Centre, Universitas Islam Bandung, Oxford College of Pharmacy, ATMS Group of Institutions, Institut Sains dan Teknologi Nasional, Mbarara University of Science and Technology, Kampala International University, Kebbi State University of Science and Technology Aliero, University Institute of Pharma Sciences Chandigarh University, and Laureate Institute of Pharmacy. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for publication in the next edition in August 2021. Wassalamu’alaikum Wr. Wb.